ZEN AESTHETICS AND GUEST EXPERIENCE: EXPLORING THE ENVIRONMENTAL AND EXPERIENTIAL IMPACTS OF ZEN-INSPIRED DESIGN IN MODERN LEISURE RESORTS - Wu, Pei Feng; Nasir, Nadia (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
This study explores the influence of Zen aesthetics on the environmental design and guest experiences within modern leisure resorts. Rooted in the principles of simplicity, harmony, and mindfulness, Zen design offers a unique framework for enhancing guest satisfaction, emotional well-being, and connection with nature. However, the increasing commercialization of Zen aesthetics poses challenges in maintaining authenticity and philosophical integrity. Through an exploratory qualitative approach, this research investigates how Zen-inspired elements—such as natural materials, minimalist spatial design, and integrated nature components—are applied in resort environments and how they affect guest perceptions and experiences. A purposive sample of 20 participants, including resort managers and guests, was selected to provide insights through semi-structured interviews. Thematic analysis revealed five major research themes: the identification of key Zen design components, their role in attracting guests, their contribution to guest tranquility, their ability to foster human-nature connection, and the impact of Zen-inspired activities on guest engagement and well-being. Results indicate that Zen design successfully promotes calmness and introspection through elements such as open spaces, earthy tones, and meditative zones. Zen-related cultural practices—like tea ceremonies, calligraphy, and yoga—were found to enrich guest experiences and encourage cultural appreciation. Despite the positive impacts, the study highlights the need for balance between modern luxury amenities and traditional Zen values. Furthermore, it emphasizes the importance of integrating sustainable practices aligned with Zen philosophy. This study contributes to both academic literature and industry application by offering a conceptual framework that links Zen aesthetics to environmental psychology, design theory, and hospitality experience. Recommendations include designing with ecological awareness, preserving cultural authenticity, and curating immersive experiences rooted in Zen philosophy. Ultimately, Zen-inspired design emerges as a transformative approach for redefining the standards of sustainable and mindful tourism in the contemporary hospitality industry.